Multiculturalism Education Is An Effort To Counteract Identity Politics - Irwan, Irwan; Yon Hendri; Wilma Sriwulan; Yurisman (Kirana Publisher (KNPub), 2023)
This research discusses the role of the state in counteracting identity politics in Indonesia. This research is a research library research. The researcher tries to collect literature related to the role of the state in counteracting identity politics. The type of this research is library research. Data collection techniques through documentation, literature, mass media. The findings of this paper are as follows, that in counteracting identity politics that occurs in society where identity politics in the name of culture and religion will become a threat to the integrity of the state. The state in this case must play an active role in counteracting identity politics so that it does not develop in society. one of the efforts made by the state is by providing an understanding to the public of the importance of multiculturalism. The plural Indonesian society is a cultural identity and is a gift from God for Indonesian society. This multicultural education needs to be developed by the state so that identity politics does not develop.